2007
DOI: 10.1007/s11071-006-9180-3
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on a beam-rigid body structure repetitively impacting a rod

Abstract: This paper investigates the experimental dynamics of a beam structure that supports an attached rigid body and that can impact a comparatively compliant base structure. The problem area is motivated by impact phenomena that are observed in certain structures internal to nuclear reactors. The assembly is subjected to base excitation at specified frequency and acceleration, and the resulting displacement and velocity time histories are recorded and used to obtain spectra, phase diagrams, and Poincaré sections. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The friction material adopted in the LUSMs is usually a material having both high hardness and wear resistance (the Al 2 O 3 ceramic, for example, is often chosen as the friction material in LUSM), the normal impacts between the stator and mover is considered as rigid impacts in this paper. The dynamics of the continuous systems such as beams, strings and robs subjected to impacts have been studied extensively [10][11][12][13][14][15]. The CoR method is an attractive and effective approach to simulate the impacts with rigid obstacle.…”
Section: Introductionmentioning
confidence: 99%
“…The friction material adopted in the LUSMs is usually a material having both high hardness and wear resistance (the Al 2 O 3 ceramic, for example, is often chosen as the friction material in LUSM), the normal impacts between the stator and mover is considered as rigid impacts in this paper. The dynamics of the continuous systems such as beams, strings and robs subjected to impacts have been studied extensively [10][11][12][13][14][15]. The CoR method is an attractive and effective approach to simulate the impacts with rigid obstacle.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of continuous systems like beams, strings, and rods subjected to impacts caused by motion-limiting constraints have been studied extensively. A representative set of studies can be found in [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The impact of these systems is modelled using two different methods.…”
Section: Introductionmentioning
confidence: 99%
“…Impacting systems are non-smooth dynamical systems in which components may experience impacts. Many experiments have been conducted on the dynamics of systems whose numerical models interchange between continuous and discrete states [12,15,21,33,42]. Strong nonlinear behavior, induced by rigid collisions, has been observed in most cases driving these systems into chaos [11].…”
Section: Introductionmentioning
confidence: 99%
“…Other attempts using explicit mapping to analyze mechanical impacting systems have also been published [7,31]. In all cases, however, disagreements have been observed between the theoretical analysis employing the above methods and various experimental studies [12,14,42,43]. More recently, numerical analysis of soft-impact oscillators employing the discontinuity-mapping approach has been proposed to study the onset of the grazing bifurcation [24,25] with results showing good agreement with experimental observations [15,25].…”
Section: Introductionmentioning
confidence: 99%